2015
DOI: 10.3389/fpls.2015.00665
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of gene action for indeterminate growth in mungbean [Vigna radiata (L.) Wilczek]

Abstract: In order to investigate the inheritance pattern of indeterminate growth in Vigna radiata, various related traits were studied. The techniques used for the purpose were generation mean and variance analyses. Narrow sense heritability estimates were also computed. Four out of fifty greengram accessions were selected during preliminary screen trial based on DDd2 and DDh2 values. Two cross combinations were made by utilizing four parents. Generation variance analysis demonstrated the engagement of additive and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Higher magnitudes of additive variance in heat-stressed conditions pointed out its potential role in inheritance of plant traits which conferred heat tolerance in maize. Higher estimates of narrow sense heritability (F 2 and F ∞ ) and genetic advance further confirmed the role of few major genes and related genetic effects and the possibility of genetic progress of studied traits (Iqbal et al, 2015 ). Both heritability and genetic advance constitute an important selection criterion.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Higher magnitudes of additive variance in heat-stressed conditions pointed out its potential role in inheritance of plant traits which conferred heat tolerance in maize. Higher estimates of narrow sense heritability (F 2 and F ∞ ) and genetic advance further confirmed the role of few major genes and related genetic effects and the possibility of genetic progress of studied traits (Iqbal et al, 2015 ). Both heritability and genetic advance constitute an important selection criterion.…”
Section: Discussionmentioning
confidence: 60%
“…Based on χ 2 values, genetic models comprising two, three, four and five parameters (additive, dominance and epistatic interactions, i.e., additive-additive, additive-dominance, dominance-dominance) were found best suited to all characters under both environments. Involvement of non-allelic gene interaction in all traits corroborated the existence of potential variation for further exploitation (Iqbal et al, 2015 ). Both additive-dominance genetic effects were recorded for all traits under both conditions except transpiration rate under non-stressed regime which was found under the influence of only additive gene action.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The NP fertilizer-treated green gram plants were stronger with a 5-fold higher survival span compared to the control Journal of Nanomaterials plant. These green gram plants produced pods after 18 days, two times faster than other literature reports on regular plants [37]. Images of the healthy second-generation plants from the NP fertilizer-treated green gram seeds are included in the SI ( Figure S5).…”
Section: Resultsmentioning
confidence: 79%
“…Iqbal et al (2015) suggested usefulness of crossing among the desirable segregants in the segregating populations for those traits where early selection cannot be exercised. Dissection of total variance into D (additive), H (dominance), E (environmental), and F (interaction) components had been used previously for genetic studies (Haq et al, 2015;Iqbal et al, 2015). Contribution of additive (D) variance in contrast to other components was much higher in all the investigated traits.…”
Section: Traitmentioning
confidence: 99%